Gary Paulsen : Author and Wilderness Adventurer - Fine, Edith Hope. (Berkeley Heights, NJ : Enslow Publishers, 2000)
A biography of the outdoor adventurer and author, whose writing includes adventure stories, historical novels, sports books, and nature stories.
Includes bibliographical references (p. 124-125) and index.
Keywords: Paulsen, Gary; American authors -- Biography